Multi‐omics analysis to characterize molecular adaptation of Entamoeba histolytica during serum stress. Issue 22 (13th September 2022) - Singh, Shashi Shekhar; Mansuri, Mohammad Shahid; Naiyer, Sarah; Kaur, Devinder; Agrahari, Mridula; Srinivasan, Sandhya; Jhingan, Gagan Deep; Bhattacharya, Alok; Bhattacharya, Sudha
Abstract: Entamoeba histolytica is responsible for dysentery and extraintestinal disease in humans. To establish successful infection, it must generate adaptive response against stress due to host defense mechanisms. We have developed a robust proteomics workflow by combining miniaturized sample preparation, low flow‐rate chromatography, and ultra‐high sensitivity mass spectrometry, achieving increased proteome coverage, and further integrated proteomics and RNA‐seq data to decipher regulation at translational and transcriptional levels. Label‐free quantitative proteomics led to identification of 2344 proteins, an improvement over the maximum number identified in E. histolytica proteomic studies. In serum‐starved cells, 127 proteins were differentially abundant and were associated with functions including antioxidant activity, cytoskeleton, translation, catalysis, and transport. The virulence factor, Gal/GalNAc‐inhibitable lectin subunits, was significantly altered. Integration of transcriptomic and proteomic data revealed that only 30% genes were coordinately regulated at both transcriptional and translational levels. Some highly expressed transcripts did not change in protein abundance. Conversely, genes with no transcriptional change showed enhanced protein abundance, indicating post‐transcriptional regulation. This multi‐omics approach enables more refined gene expression analysis to understand the adaptive response of E. histolytica during growth stress.